1983
DOI: 10.1128/iai.39.1.463-465.1983
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Immune Response in Acquired Immunity to Chlamydial Genital Infection of Female Guinea Pigs

Abstract: Immunity to reinfection in the genital tract of female guinea pigs with the agent of guinea pig inclusion conjunctivitis was found to be dependent upon an intact humoral immune response. Cell-mediated immunity in the absence of humoral immunity had no apparent role in resistance to challenge infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 7 publications
1
38
1
Order By: Relevance
“…It is not difficult to conceive that women can become infected in the GI tract even in the absence of anal intercourse via fluid contamination of the rectum from the vagina or through oral sexual activity. Studies in all animal models demonstrate that genital infection resolves within several weeks through the development of a Th1 cell-mediated immune response (Rank, 2006). However, because T cells do not remain in the genital tract following recovery, the individual becomes susceptible to reinfection (Igietseme & Rank, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…It is not difficult to conceive that women can become infected in the GI tract even in the absence of anal intercourse via fluid contamination of the rectum from the vagina or through oral sexual activity. Studies in all animal models demonstrate that genital infection resolves within several weeks through the development of a Th1 cell-mediated immune response (Rank, 2006). However, because T cells do not remain in the genital tract following recovery, the individual becomes susceptible to reinfection (Igietseme & Rank, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…However, in laboratory animals other than the mouse there has been controversy for a number of years over the relative role of antibody or cell mediated immunity in protection. Few of these experiments could be regarded as definitive from a modern perspective, but it appears that in the guinea pig specific antibodies may play a more prominent role in protection compared to the mouse [23,[26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…While immunity appears to develop following a primary chlamydial genital infection, it is short-lived and individuals can be reinfected (4,17). Analyses of hosts' antichlamydial immune mechanisms in animal models have shown that in guinea pigs both humoral immunity (15,21) and cell-mediated immunity (16,20) are essential for resolution of and resistance to infection. However, in the murine system, several lines of evidence suggest that T-cell-mediated immunity is the principal immune mechanism for controlling chlamydial genital disease.…”
mentioning
confidence: 99%